2007
DOI: 10.1192/bjp.bp.106.027136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of barriers on the Clifton suspension bridge, England, on local patterns of suicide: implications for prevention

Abstract: We assessed the effect of the installation of barriers on the Clifton suspension bridge, Bristol, England, in 1998 on local suicides by jumping. Deaths from this bridge halved from 8.2 per year (1994-1998) to 4.0 per year (1999-2003; P=0.008). Although 90% of the suicides from the bridge were by males, there was no evidence of an increase in male suicide by jumping from other sites in the Bristol area after the erection of the barriers. This study provides evidence for the effectiveness of barriers on bridges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 6 publications
5
56
0
5
Order By: Relevance
“…Recent studies have revealed that erecting fences or barriers at hot spot jumping sites is effective in reducing the number of suicides by jumping 13 18 19. Sadly, there is evidence illustrating that the removal of safety barriers in a central city bridge in an Australian metropolitan area in 1996 resulted in a substantial increase in the number of suicide deaths by jumping from the bridge 20.…”
Section: Implications For Preventionmentioning
confidence: 99%
“…Recent studies have revealed that erecting fences or barriers at hot spot jumping sites is effective in reducing the number of suicides by jumping 13 18 19. Sadly, there is evidence illustrating that the removal of safety barriers in a central city bridge in an Australian metropolitan area in 1996 resulted in a substantial increase in the number of suicide deaths by jumping from the bridge 20.…”
Section: Implications For Preventionmentioning
confidence: 99%
“…Physical barriers are effective in reducing suicides at particular jumping sites, although evidence regarding displacement of suicides to other sites remains inconclusive. [41][42][43][44] Preventing access to the means of suicide does not, however, address individual psychological distress. Other interventions, such as depression screening and treatment, are likely to be important for reducing high suicide rates in urban and rural areas.…”
Section: Implications For Research and Preventionmentioning
confidence: 99%
“…Placing barriers at known suicide locations (e.g. certain bridges) is another effective method for deterring selfharm and suicide, as a significant number of people who are deterred or delayed in this fashion will re-consider their suicidal thoughts and many will not proceed to find other means of self-harm (Bennewith et al 2007;Zalsman et al 2016).…”
Section: Interventions At the Level Of The Individualmentioning
confidence: 99%